CSR Impact on Hospital Duopoly with Price and Quality Competition - Youguang Xu (Journal of Applied Mathematics)
This paper investigates the impact of corporate social responsibility (CSR) on hospital duopoly with price and quality competition. A CSR hospital is defined in this paper that cares about not only the profit but also the patient benefit. We start our analysis by establishing a two-stage Hotelling model with and without CSR. Results indicate that privatization mechanism may not be the best way of improving medical quality. Competition between hospitals with zero-CSR would lower the equilibrium qualities compared to the first-best level. So the coexistence of a public (more accurately, partial public) and a private hospital might be more efficient than a private-private hospital duopoly. During the competition with CSR in price and quality, social welfare level acts in accordance with an inverted U-shaped trajectory as CSR degree increases. The main reason lies in tha fact that optimal degree of CSR is determined by the trade-off between the benefit of quality improvement and the cost of quality investment. Numerical simulation shows that the optimal degree of CSR is less than a third.